In silico analysis of heme binding effect on the formation of mouse arginyl-tRNA-protein transferase 1 and protein LIAT1 complex - Бараннік, Т. В.; Федорова, А. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Ab initio prediction of mouse arginyl-tRNA-protein transferase 1 (R-transferase, EC 2.3.2.8) and protein LIAT1 structures was performed by I-Tasser server. Molecular docking studies of the protein models revealed that potential heme binding sites didn’t coincide with the sites of interaction with protein partner in both R-transferase and LIAT1 protein. Heme docking to the complex of two proteins showed LIAT1 protein to provide more preferable sites for heme binding than R-transferase. Heme attachment to the cavities in the core of R-transferase involved in catalysis and the alterations of LIAT1 protein conformation could be the additional mechanisms of heme inhibiting action on protein arginylation.